Did the Tax Cuts Increase Hours of Work? A Pre-Post Analysis of Swedish Panel Data - Anders Klevmarken (Uppsala University, Department of Economics, 1997)
Based on longitudinal data covering periods before and after the major Swedish tax reform in 1991 a difference-in-difference approach is used to estimate the effects on hours of work of the cuts in the income tax. The results show that women increased their hours more than men did. If there is an effect for men at all, then primarily young men have adjusted to the new tax incentives.
urn:nbn:se:uu:diva-2389
Keywords: 330